UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING DI KELAS XI ATPH SMKN 8 PEKANBARU SEMESTER GANJIL TAHUN PELAJARAN 2022/2023 - RENI WIDIASTUTI (JURNAL ILMIAH MAKSITEK, 2022)
The problem in this study is that students do not understand and master the material. In addition, the use of learning methods that are still conventional makes students less active in participating in existing learning so that students only know something and are not able to do something, so the learning process does not run effectively. This study aims to describe efforts to improve student learning outcomes in nursery and plant tissue culture learning materials through discovery learning models in class XI ATPH SMKN 8 Pekanbaru. This type of research is classroom action research. This research was conducted at SMKN 8 Pekanbaru. The research was conducted in two cycles with 4 (four) stages, namely planning, implementing, observing, and reflecting. The subjects in this study were 25 class XI students at SMKN 8 Pekanbaru. Data collection techniques through class observation and documentation. The data analysis technique that guides data processing uses the percentage (%) technique. The results of this study show that student learning outcomes using the discovery learning learning model increase at each meeting. Student learning outcomes in cycle I amounted to 75, which increased in cycle II to 85. Not only that, students were very enthusiastic about solving problems and the results of the learning were shown by the very good grades obtained from the evaluation at the end of the lesson. This proves that using the discovery learning learning model can improve the learning outcomes of class XI ATPH students at SMKN 8 Pekanbaru.